2004
DOI: 10.1063/1.1638637
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional scanning tunneling microscopy and spectroscopy of InGaP/GaAs heterojunctions

Abstract: Compositionally abrupt InGaP/GaAs heterojunctions grown by gas-source molecular beam epitaxy have been investigated by cross-sectional scanning tunneling microscopy and spectroscopy. Images inside the InGaP layer show non-uniform In and Ga distribution. About 1.5 nm of transition region at the interfaces is observed, with indium carryover identified at the GaAs-on-InGaP interface. Spatially resolved tunneling spectra with nanometer spacing across the interface were acquired, from which band offsets (revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…It thus means that, after GalnP and AHnP layer growth, the In carry-over effect takes place and In atoms tend to segregate at the surface, in such way that they will likely incorporate into the GaAs outer layer. This is a well-known phenomenon described by several authors for the interface GaAs/GalnP [4, 6,22,23]. According to our results, In atoms in the GaAs/AllnP interface would exhibit the same behavior.…”
Section: Interfacesupporting
confidence: 58%
See 2 more Smart Citations
“…It thus means that, after GalnP and AHnP layer growth, the In carry-over effect takes place and In atoms tend to segregate at the surface, in such way that they will likely incorporate into the GaAs outer layer. This is a well-known phenomenon described by several authors for the interface GaAs/GalnP [4, 6,22,23]. According to our results, In atoms in the GaAs/AllnP interface would exhibit the same behavior.…”
Section: Interfacesupporting
confidence: 58%
“…Studies of the GaAs/GalnP interface have revealed the formation of GalnAs, mainly caused by the incorporation of In atoms into the subsequent GaAs layer [6,7]. The presence of quaternary phases like GalnAsP is also feasible; however XPS is not able to assert its presence since Ga 2p, As 3d, In 3d and P 2p core levels do not show contributions different to those appearing in the GaAs and the GalnP layers.…”
Section: Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the extensive studies of the interface control, there is no general agreement upon the dominant mechanism governing the interface formation, probably due to differences in reactor configuration. 2,6,8,9 It has been shown that the interface layers at the two interfaces, i.e., ''GaAs on InGaP'' and ''InGaP on GaAs,'' formed during the metalorganic chemical vapor deposition (MOCVD) growth are not equivalent with respect to their structural, electrical, and optical properties and that the layer formed at the interface of ''GaAs-onInGaP'' has a much smaller bandgap. The reason has been thought to be the In carry-over effect and the lower incorporation efficiency of PH 3 as compared with AsH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the performance of InGaP/GaAs-based devices, research on controlling the interface quality has been reported since the 1980s. 2,[6][7][8][9] Through controlling the switching sequence of source gases at the interfaces during the growth interruption between layers, In and As carry-over and arsenic-phosphorus exchange at the interfaces have been extensively investigated. In spite of the extensive studies of the interface control, there is no general agreement upon the dominant mechanism governing the interface formation, probably due to differences in reactor configuration.…”
Section: Introductionmentioning
confidence: 99%